Using the scoring schemes in the right way: the dynamic assessment of stroke and bleeding risk in patients with atrial fibrillation - Chao, Tze-Fan; Chen, Shih-Ann (Journal of Thoracic Disease; Vol 10, Supplement 17 (June 20, 2018): Journal of Thoracic Disease, 2018)
Atrial fibrillation (AF) is an important risk factor of ischemic stroke (1), and stroke prevention is the cornerstone for the AF management. The decision about the prescriptions of oral anticoagulants (OACs) should be based on the stroke risk of each AF patients. Also, the bleeding risk of anticoagulated patients should be evaluated, so that closer follow-up could be arranged for those who are potentially at risk, and modifiable bleeding risk factors could be corrected.